Strongyloides westeri infection on a Thoroughbred breeding farm in Ireland (2014–2019): Prevalence, risk factors and peripartum ivermectin. (28th November 2022) - Kirtland, Abbe; McAloon, Conor; Walshe, Nicola; Duggan, Vivienne
Summary: Background: The mean proportion of Strongyloides westeri ( S. westeri ) infected foals on Thoroughbred breeding farms in central Kentucky has been reported as 30%. The prevalence of S. westeri in Ireland and the effect of peripartum ivermectin treatment of the dam are unknown. Objectives: The objectives of the study were to determine the proportion of foals infected and the prevalence of positive S. westeri faecal egg count (FEC) tests within defined age groups on a Thoroughbred breeding farm in Ireland between 2014 and 2019 inclusive and, furthermore, to identify risk factors for infection and the effect of peripartum ivermectin treatment. We hypothesised no significant difference in S. westeri infection in progeny <365 days of age, where the dam received peripartum ivermectin treatment between 30 days pre‐ and 7 days post‐foaling, versus no treatment. Study design: Retrospective observational cohort. Methods: Farm records of 1420 FECs for 459 foals were reviewed. Positive test prevalence and proportion of foals infected were determined using days between birth and each FEC result, up to 365 days. A mixed effects logistic regression model was constructed to examine the association between date of sample collection, year, age at sampling, peripartum dam ivermectin treatment and S. westeri patent infection in progeny <365 days of age. Results: Test prevalence and proportion of foals infected increased from 0.09 to 0.43 and 0.17 to 0.52, respectively. The risk of positive S. westeri infection was linearly and positively associated with day of the year (OR = 1.75; 95% CI: 1.14, 2.7; p = 0.01) and negatively associated with age (OR = 0.37; 95% CI: 0.23, 0.59; p = <0.001). Peripartum ivermectin treatment was associated with reduced S. westeri infection in progeny <365 days of age (OR = 0.24; 95% CI: 0.07, 0.79; p = 0.02). Main limitations: Faecal egg counts performed by trained lay personnel. Dynamic population. Conclusions: Increasing prevalence of S. westeri infection may reflect cumulative environmental contamination.